Understanding Home Hemodialysis Patient Attrition: A Cohort Study. (June 2021) - Paterson, Bailey; Fox, Danielle E.; Lee, Chel Hee; Riehl-Tonn, Victoria; Qirzaji, Elena; Quinn, Rob; Ward, David; MacRae, Jennifer M.
Background: Home hemodialysis (HHD) offers a flexible, patient-centered modality for patients with kidney failure. Growth in HHD is achieved by increasing the number of patients starting HHD and reducing attrition with strategies to prevent the modifiable reasons for loss. Objective: Our primary objective was to describe a Canadian HHD population in terms of technique failure and time to exit from HHD in order to understand reasons for exit. Our secondary objectives include the following: (1) determining reasons for training failure, (2) reasons for early exit from HHD, and (3) timing of program exit. Design: A retrospective cohort study of incident adult HHD patients between January 1, 2013—June 30, 2020. Setting: Alberta Kidney Care South, AKC-S HHD program. Participants: Patients who started training for HHD in AKC-S. Methods: A retrospective, cohort study of incident adult HHD patients with primary outcome time on home hemodialysis, secondary outcomes include reason for train failure, time to and reasons for technique failure. Cox-proportional hazard model to determine associations between patient characteristics and technique failure. The cumulative probability of technique failure over time was reported using a competing risks model. Results: A total of 167 patients entered HHD. Training failure occurred in 20 (12%), at 3.1 [2.0, 5.5] weeks; these patients were older ( P < .001) and had 2 or more comorbidities ( P < .001). Reasons for HHD exit after training included transplant (35; 21%), death (8; 4.8%), and technique failure (24; 14.4%). Overall, the median time to HHD exit, was 23 months [11, 41] and the median time of technique failure was 17 months [8.9, 36]. Reasons for technique failure included: psychosocial reasons (37%) at a median time 8.9 months [7.7, 13], safety (12.5%) at 19 months [19, 36], and medical (37.5%) at 26 months [11, 50]. Limitations: Small patient population with quality of data limited by the electronic-based medical record and non-standardized definitions of reasons for exit. Conclusions: Training failure is a particularly important source of patient loss. Reasons for exit differ according to duration on HHD. Early interventions aimed at reducing train failure and increasing psychosocial supports may help program growth.